Initial LDH level can predict the survival benefit from bevacizumab in the first-line setting in Chinese patients with metastatic colorectal cancer - Yin, Chenxi (Dove Medical Press, 2014)
BACKGROUND: Markers to predict the efficacy of bevacizumab treatment have been not fully validated in most cancers, including metastatic colorectal cancer (mCRC). The aim of this study was to investigate the potential role of lactate dehydrogenase (LDH) in predicting the survival benefit from first-line bevacizumab treatment, in Chinese patients with mCRC. METHODS: All the patients were diagnosed with mCRC at the Sun Yat-sen University Cancer Center from 2003 to 2013. The study group and the control group were classified by receiving bevacizumab or not. The serum LDH value of all the patients had been detected before the first-line treatment. The primary end point was progression-free survival (PFS). RESULTS: The median PFS of the study and the control group (patients who received bevacizumab or not) was 11.3 and 9.1 months, respectively (P=0.004). In the control group, the median PFS of the high LDH level and the low LDH level groups was 6.9 and 10.2 months, respectively (P<0.001). However, in the study group, the corresponding median PFS was 9.9 and 11.9 months, respectively (P=0.145). In addition, for the low LDH level group, the median PFS was 11.9 and 10.2 months for patients who received bevacizumab or not, respectively (P=0.066); however, the median PFS of patients receiving bevacizumab or not was significantly different in the high LDH level group (9.9 and 6.9 months, respectively) (P=0.012). CONCLUSION: The addition of bevacizumab in the first-line treatment setting could improve the PFS of mCRC patients notably. However, the benefit could only be potentially reflected on patients with high serum LDH level.